A Novel Generic Autonomous Synchronization Method for Microgrids - Hasan K. Alrajhi (IEEE Access)
This research paper proposes a novel generic synchronization method for microgrids that addresses the key limitations of existing approaches. The method enables seamless synchronization and reconnection across multiple microgrid operating scenarios without relying on communication infrastructure or phase-locked loops (PLLs). It can synchronize islanded microgrids with grid-connected systems, interconnect multiple islanded microgrids, and facilitate smooth transitions between operating modes. Notably, the approach maintains system stability and works effectively under both balanced and unbalanced conditions, including short circuits. The proposed technique is implemented at circuit breaker terminals and requires no modifications to the underlying converter control loops. This preserves system stability while enabling plug-and-play capability. The method also provides inherent protection features, automatically disconnecting during faults and re-synchronizing after fault clearance. Comprehensive simulations in PSCAD/EMTDC validate the approach across multiple test systems and operating scenarios. Results demonstrate the method’s effectiveness for synchronization, re-synchronization, and seamless mode transitions in various microgrid configurations including synchronizing multipoles microgrids with the IEEE 14-bus benchmark. The proposed generic synchronization technique represents a significant advancement in microgrid control, enhancing reliability and resiliency without compromising stability or requiring complex communication systems.